DISASTER MITIGATION THROUGH ENVIRONMENTAL LEADERSHIP IN SMP NEGERI 2 BULAWA, BONE BEACH - Irka Priwanda Tumelap; Fasya Ramadhan Hemeto; Ulfanna Paputungan; Alya Sri Andini Rivai; Abdul Rahmat; Ronal Hutagalung (Scholar Express Journal, 2022)
Disaster is an series of incidents that results in victims of human suffering, loss of property, damage to the environment, facilities and infrastructure and can cause disruption to the life system and people's livelihoods. Basically a natural disaster is an incident that cannot be avoided, but humans can prevent and prepare themselves before the disaster suddenly comes. In carrying out this leadership project, we used a socialization method with a qualitative approach to students at SMP Negeri 2 Bulawa regarding flood disaster mitigation, as well as tree planting actions which are expected to provide an understanding of the importance of disaster mitigation from an early age and foster a sense of love for the environment.
Keywords: Leadership; Outreach; Disaster Mitigation; Environmental Preservation